THE EFFECTS OF AROMATHERAPY CANDLES AS A COMPLEMENTARY THERAPY FOR SLEEP DISTURBANCES: A LITERATURE REVIEW - Abdullah, Dessy; Maryetti Marwazi,; Fitra Deny,; Elfi Yulfienti, (Nusantara Hasana Journal, 2024)
Aromatherapy, the use of essential oils derived from plants, has gained increasing attention as a complementary therapy for various health conditions. One specific application of aromatherapy is the use of aromatic candles to aid in the management of sleep disturbances. This literature review examines the existing research on the effects of aromatherapy candles as a complementary therapy for sleep disorders. The review synthesizes findings from multiple studies to assess the efficacy of this approach and explores the potential mechanisms by which aromatherapy candles may improve sleep quality. The review also discusses the practical considerations and limitations of using aromatherapy candles as a sleep intervention. Overall, the literature suggests that aromatherapy candles may have a positive impact on sleep, though more robust and standardized research is needed to fully understand their therapeutic potential in this context.